2016
DOI: 10.3390/toxins8070209
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Toxins and Diabetic Foot Ulcers: Role in Pathogenesis and Interest in Diagnosis

Abstract: Infection of foot ulcers is a common, often severe and costly complication in diabetes. Diabetic foot infections (DFI) are mainly polymicrobial, and Staphylococcus aureus is the most frequent pathogen isolated. The numerous virulence factors and toxins produced by S. aureus during an infection are well characterized. However, some particular features could be observed in DFI. The aim of this review is to describe the role of S. aureus in DFI and the implication of its toxins in the establishment of the infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 176 publications
(235 reference statements)
9
119
1
3
Order By: Relevance
“…In this study, bacteria were recovered from the wounds of 83% of the sampled diabetic patients, indicating the high prevalence of bacteria in the wounds of diabetic patients, as in agreement with Dunyach-Remy et al, [26]. The recovery of bacteria in diabetic wounds is one of the signs of infection along with clinical symptoms such as erythema, pain, tenderness and pus [9].The wounds were in the lower limbs in 94% of the cases and this in literature has been attributed to the vascular permeability that causes impaired blood supply to the peripheries during a diabetic state [27] and can result to limb amputations [7].The wounds were also noted mostly in the elderly (> 60 year) of which whose immune system is already compromised due to ageing [28] and diabetes thereby increasing the risk of bacterial infections [29] Biochemical tests are solely based on phenotypic properties of bacteria which are shared by most species [12,13,17], as a result misidentification is common, which can also account for the anomalies observed in table 3-5 whereby culture-based methods of identification (API) misinterpreted some of the results which were confirmed to be different by the 16S rDNA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, bacteria were recovered from the wounds of 83% of the sampled diabetic patients, indicating the high prevalence of bacteria in the wounds of diabetic patients, as in agreement with Dunyach-Remy et al, [26]. The recovery of bacteria in diabetic wounds is one of the signs of infection along with clinical symptoms such as erythema, pain, tenderness and pus [9].The wounds were in the lower limbs in 94% of the cases and this in literature has been attributed to the vascular permeability that causes impaired blood supply to the peripheries during a diabetic state [27] and can result to limb amputations [7].The wounds were also noted mostly in the elderly (> 60 year) of which whose immune system is already compromised due to ageing [28] and diabetes thereby increasing the risk of bacterial infections [29] Biochemical tests are solely based on phenotypic properties of bacteria which are shared by most species [12,13,17], as a result misidentification is common, which can also account for the anomalies observed in table 3-5 whereby culture-based methods of identification (API) misinterpreted some of the results which were confirmed to be different by the 16S rDNA.…”
Section: Discussionsupporting
confidence: 92%
“…P. aeruginosa possesses virulence factors such as exoproteases, siderophores, exotoxins, hydrogen cyanide and pyocyanin that attack host defenses and impair wound healing [35] while S. aureus possess factors such as coagulase, catalase and clumping factors that play a role in infection mainly occurring in immuno-compromised individuals such as diabetic individuals [9]. S. aureus has a role in deepening and spreading infections in body tissue by damaging the host cell membranes and causing cell lysis [26], which can be also attributed to diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The reported concentration of pyruvate ranges from 40 μM in individual cells to 10 mM in the blood of people with diabetes ( 42 45 ). Interestingly, diabetic patients have a higher propensity for pneumonia and foot infections caused by S. aureus ( 46 48 ). Additionally, it has been reported that diabetic mice showed a significantly higher bacterial burden after being challenged with S. aureus and had an impaired ability to clear the infection relative to nondiabetic mice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the last group of toxins is called epidermal differentiation inhibitor (EDIN). These toxins target host Rho GTPases, favoring bacterial dissemination in tissues [116].…”
Section: Virulence Of Mrsa-st80mentioning
confidence: 99%